Cover Image, Volume 36, Issue 5. (13th April 2023) - Wang, Nian; Maharjan, Surendra; Tsai, Andy P.; Lin, Peter B.; Qi, Yi; Wallace, Abigail; Jewett, Megan; Liu, Fang; Landreth, Gary E.; Oblak, Adrian L.
Abstract : The featured cover image is based on the Research Article Integrating multimodality magnetic resonance imaging to the Allen Mouse Brain Common Coordinate Framework by Nian Wang et al., https://doi.org/10.1002/nbm.4887 .